Green Planning of Cities and Communities: Theories, Strategies and Tools of a Complex Framework. - Dall’O’, Giuliano (Springer, 2020)
If urban planning plays a fundamental role in the future of humanity, which is concentrating an increasing share of the population in cities, then green planning is the most effective response to the climate change emergency. This chapter analyses theories, strategies and tools that characterize the green planning of cities and communities useful for understanding and managing its complexity. The first section analyses the continuously evolving relationship between urban planning and sustainable development. The topic of sustainable development in green planning is seen as a comparison between two approaches, one more utopian and idealistic and one more pragmatic, both in the two fundamental declinations: the more anthropocentric and the more ecological. Subsequently, the more applicative aspects are dealt with: from the analysis of the sectoral planning tools, relations and synergies are highlighted with the aim of providing an integrated, inclusive model. The final part of the chapter proposes a planning strategy aimed at supporting a structured, integrated and effective green planning model for cities and communities.
Keywords: Grünplanung; Stadtplanung; Klimawandel; Klimaanpassung; Nachhaltige Stadtentwicklung; Fachplanung; Synergieeffekt